2020
DOI: 10.32794/mr11250067
|View full text |Cite
|
Sign up to set email alerts
|

ER stress and autophagy induced by SARS-CoV-2: The targets for melatonin treatment

Abstract: Coronavirus disease 19 (COVID-19) is a viral disease caused by the new coronavirus SARS-CoV-2. Like other coronaviral infections, SARS-CoV-2 causes oxidative and ER stress triggering cellular response pathways, mainly PERK and IRE1 branches of the UPR. This excessive oxidative stress and the increasing of unfolded and misfolded proteins induce autophagy. Once this process is triggered, the blockage of the fusion of autophagosomes and lysosomes induced by virus leads to an incomplete autophagy. Double-membraned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 113 publications
0
10
0
Order By: Relevance
“…Melatonin is a naturally occurring molecule assumed to be present in every species [ 19 ]. Due to its antioxidant, anti-inflammatory, as well as other properties [ 20 , 21 , 22 , 23 , 24 , 25 ], it has been speculated to be a promising molecule for treating COVID-19 patients [ 18 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and also other deadly viral infectious diseases [ 48 , 49 , 50 , 51 ]. A small scale clinical trial has also shown promising results [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is a naturally occurring molecule assumed to be present in every species [ 19 ]. Due to its antioxidant, anti-inflammatory, as well as other properties [ 20 , 21 , 22 , 23 , 24 , 25 ], it has been speculated to be a promising molecule for treating COVID-19 patients [ 18 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], and also other deadly viral infectious diseases [ 48 , 49 , 50 , 51 ]. A small scale clinical trial has also shown promising results [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is known that SARS-CoV-2 (like other human coronaviruses) can hamper the unfolded protein response (UPR) and consequently the induction of autophagy in order to improve its replicative capacity. In this perspective, a very intriguing therapeutic strategy could be to unlock the virus induced autophagy blockage, thus decreasing viral replication capacity ( Boga and Coto-Montes, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, significant XBP1 splicing and increased apoptosis levels have been detected in infected cells with recombinant SARS-CoV-2 containing the missing E protein. As far as ATF6 is concerned, SARS-CoV-2-induced induction in these branches has not been reported [ 55 ]. Therefore, further research on UPR affected by the coronaviruses may also help identify new strategies for antiviral treatments and led to the development of more effective anti-coronavirus vaccines.…”
Section: Coronavirus-induced Er Stress Response Activates the Uprmentioning
confidence: 99%
“…Melatonin stimulates UPR and unlocks autophagy blockage, allowing the formation of autophagolysosomes, which results in complete autophagy and a decrease in viral replication capacity. In addition, Melatonin has been reported to show protective effects against some drugs and toxins, making the combined therapy more effective [ 55 , 71 ]. In short, coronavirus replication leads to ER stress and UPR induction.…”
Section: Coronavirus-induced Er Stress Response Activates the Uprmentioning
confidence: 99%